EMERGENCY CONDITIONS AT THE CHILDREN'S RECEPTION - Inogamov Sherzod Muhamatisakovich (Sciental Journals Publishing, 2025)
Schwinke's edema is an immediate allergic reaction, manifested by angioedema spreading to the skin, subcutaneous tissue, and mucous membranes.